Development of an Integrated Problem-Based Learning (PBL) Online-Based Learning Model to Improve the Feasibility and Effectiveness of Physics Learning - Sofvan; Herpratiwi; Fitri, Dina Martha (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aimed to develop, validate, and evaluate the feasibility and effectiveness of a Google Sites–based e-Module integrated with the Problem-Based Learning (PBL) model in improving physics learning outcomes of Grade XII students on dynamic electricity material. A Research and Development (R&D) design following the Borg and Gall framework was employed, encompassing needs analysis, product design, development, expert validation, revision, and trial stages. Expert validation involved material, media, and design specialists. Feasibility was evaluated through small-group (n = 6) and large-group (n = 12) practicality trials using a five-point Likert-scale questionnaire. Effectiveness was measured via pre-test and post-test instruments, with improvement calculated using the normalized gain (N-Gain) formula. Instrument reliability was confirmed with Cronbach's Alpha values of 0.905 (pre-test) and 0.861 (post-test). Expert validation yielded average scores of 93.46% (material), 93.75% (media), and 86.50% (design), all classified as